Longitudinal association between concurrent changes in social support and mental health symptoms among low-income U.S. veterans: a 2-year follow-up study - Jack Tsai; Bijeta Pradhan; Md Faruk Hossain; Vahed Maroufy (Psychiatric Quarterly, 2026)
Abstract Social support is known to be able to buffer against psychological stressors, but further study is needed on how different types of social support and mental health change together over time, especially in special populations like U.S. veterans. Social support can also be divided into four types: Emotional Support/Informational Support, Positive Social Interaction, Tangible Support, and Affectionate Support. Using a longitudinal, nationally representative sample of 735 low-income U.S. veterans over 2 years (2021–2023), this study examined the association between changes in these four types of social support in relation to changes in symptoms of major depression, generalized anxiety disorder, posttraumatic stress disorder, alcohol use disorder, and overall physical and mental health-related quality of life. The results found that decreased Emotional/Informational Support, Positive Social Interaction, and Tangible Support were all associated with decreases in depressive symptoms. In contrast, changes in the four types of social support were not associated with changes in other mental health symptoms. Together, these findings indicate the important role that social support may play, specifically in major depression, and underlines the importance of helping low-income U.S. veterans develop strong social networks.